Large Scale Renewable Power Generation Advances in Technologies for Generation, Transmission and Storage - Hossain, Jahangir; Mahmud, Apel.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2014)
This book focuses on the issues of integrating large-scale renewable power generation into existing grids. The issues covered in this book include different types of renewable power generation along with their transmission and distribution, storage, and protection. It also contains the development of medium voltage converters for step-up-transformer-less direct grid integration of renewable generation units, grid codes and resiliency analysis for large-scale renewable power generation, active power and frequency control, and HVDC transmission. The emerging SMES technology for controlling and integrating large-scale renewable power systems is also discussed. Since the protection issues with large-scale distributed renewable power systems are different compared to the existing protection system for one way power flow, this book includes a new protection technique for renewable generators along with the inclusion of current status of smart grid. This book is a good reference for the researchers who are working the area of renewable power generation and smart grids.
Taxonomy of Uncertainty Modeling techniques in Renewable Energy System Studies -- Probabilistic Modeling and Statistical Characteristics of Aggregate Wind Power -- Conversion Efficiency Improvement in GaAs Solar Cells -- Emerging SMES Technology into Energy Storage Systems and Smart Grid Applications -- Multilevel Converters for Step-up-Transformer-less Direct Integration of Renewable Generation Units with Medium Voltage Smart Microgrids -- A Review of Interconnection Rules for Large Scale Renewable Power Generation -- Resiliency Analysis of Large-Scale Renewable Enriched Power Grid – A Network Percolation Based Approach -- Frequency Control and Inertial Response Schemes for the Future Power Networks -- Active Power and Frequency Control Considering Large Scale RES -- Impact of Large Penetration of Correlated Wind Generation on Power System Reliability -- HVDC Transmission for Offshore Wind Farm -- Wind Farm Protection -- Wind Power Plants and FACTS devices influence in the performance of distance relays -- Protection Schemes for Meshed VSC-HVDC Transmission Systems for Large-Scale Offshore Wind Farms -- Control of Emerging Brushless Doubly-Fed Reluctance Wind Turbine Generators -- Energy Hub Management with Intermittent Wind Power -- Adopting the IEC Common Information Model to Enable Smart Grid Interoperability and Knowledge Representation Processes.
Keywords: Renewable energy resources; Energy systems; Electronics; Microelectronics; Energy policy; Energy and state; Physical measurements; Measurement .; Renewable and Green Energy; Energy Systems; Energy Systems; Electronics and Microelectronics, Instrumentation; Energy Policy, Economics and Management; Measurement Science and Instrumentation